The Blood-Brain Barrier Breakdown During Acute Phase of the Pilocarpine Model of Epilepsy Is Dynamic and Time-Dependent - Mendes, Natália Ferreira; Pansani, Aline Priscila; Carmanhães, Elis Regina Ferreira; Tange, Poliana; Meireles, Juliana Vieira; Ochikubo, Mayara; Chagas, Jair Ribeiro; da Silva, Alexandre Valotta; Monteiro de Castro, Glaucia; Le Sueur-Maluf, Luciana (Frontiers in Neurology, 2019)
The maintenance of blood-brain barrier (BBB) integrity is essential for providing a suitable environment for nervous tissue function. BBB disruption is involved in many central nervous system diseases, including epilepsy. Evidence demonstrates that BBB breakdown may induce epileptic seizures, and conversely, seizure-induced BBB disruption may cause further epileptic episodes. This study was conducted based on the premise that the impairment of brain tissue during the triggering event may determine the organization and functioning of the brain during epileptogenesis, and that BBB may have a key role in this process. Our purpose was to investigate in rats the relationship between pilocarpine-induced status epilepticus (SE), and BBB integrity by determining the time course of the BBB opening and its subsequent recovery during the acute phase of the pilocarpine model. BBB integrity was assessed by quantitative and morphological methods, using sodium fluorescein and Evans blue (EB) dyes as markers of the increased permeability to micromolecules and macromolecules, respectively. Different time-points of the pilocarpine model were analyzed: 30 min after pilocarpine injection and then 1, 5, and 24 h after the SE onset. Our results show that BBB breakdown is a dynamic phenomenon and time-dependent, i.e., it happens at specific time-points of the acute phase of pilocarpine model of epilepsy, recovering in part its integrity afterwards. Pilocarpine-induced changes on brain tissue initially increases the BBB permeability to micromolecules, and subsequently, around 5 h after SE, the BBB breakdown to macromolecules occurs. After BBB breakdown, EB dye is captured by damaged cells, especially neurons, astrocytes, and oligodendrocytes. Although the BBB permeability to macromolecules is restored 24 h after the start of SE, the leakage of micromolecules persists and the consequences of BBB degradation are widely disseminated in the brain. Our findings reveal the existence of a temporal window of BBB dysfunction in the acute phase of the pilocarpine model that is important for the development of therapeutic strategies that could prevent the epileptogenesis.